Low Complexity Versatile Video Coding (VVC) for Low Bitrate Applications - Aklouf, Mourad; Leny, Marc; Dufaux, Frederic; Kieffer, Michel (European Workshop on Visual Information Processing, 2019)
The new Versatile Video Coding (VVC) standard is currently under development, targeting more efficient compression, especially for 4K and 8K contents. Nevertheless, some application scenarios still require low resolution and low bitrate encoding, e.g., live video streaming over unstable bandwidth-limited wireless networks. In addition, embedded applications also require low complexity and low power consumption solutions. As VVC is not designed for these conditions, it may not necessarily achieve the optimal tradeoff between complexity and compression efficiency. This paper proposes an optimization framework to determine the efficiency at low-resolution and low-bitrate of some of the new coding tools introduced in VVC. We show that in such coding conditions, significant reduction in terms of encoding complexity (up to 56% at 384 × 216 resolution) may be obtained by disabling some of the VVC coding tools, with a negligible impact in terms of compression efficiency (less than 1.88% increase in BD rate ).